2017
DOI: 10.1289/ehp793
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Use and Age-Related Macular Degeneration in the Agricultural Health Study

Abstract: Background:Age-related macular degeneration (AMD) is a leading cause of blindness in developed countries. Few studies have investigated its relationship to environmental neurotoxicants. In previous cross-sectional studies, we found an association between pesticide use and self-reported retinal degeneration.Objective:We evaluated the association of pesticide use with physician-confirmed incident AMD.Methods:The Agricultural Health Study (AHS) is a prospective cohort of pesticide applicators and their spouses en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The present study highlighted a possible toxic mechanism in EMAP with a higher incidence observed in regions with industrialized or farming activities, and a toxic exposure during professional life. In AMD, fungicides may increase the risk of retinal degeneration based on the Agricultural Health Study of farm families from Iowa and North Carolina (1993–1997) 18 , 19 . The role of long-term/low-dose exposure to pesticides (organophosphates, paraquat) is well documented in Parkinson disease, which is the consequence of a degeneration preferentially affecting the dopamine-synthesizing neurons of the nigrostriatal neuronal pathway 20 – 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study highlighted a possible toxic mechanism in EMAP with a higher incidence observed in regions with industrialized or farming activities, and a toxic exposure during professional life. In AMD, fungicides may increase the risk of retinal degeneration based on the Agricultural Health Study of farm families from Iowa and North Carolina (1993–1997) 18 , 19 . The role of long-term/low-dose exposure to pesticides (organophosphates, paraquat) is well documented in Parkinson disease, which is the consequence of a degeneration preferentially affecting the dopamine-synthesizing neurons of the nigrostriatal neuronal pathway 20 – 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiologic studies have shown that chronic, low-dose exposure to OPs and PYRs was associated with neurological outcomes (e.g., neurodevelopment in children, Parkinson’s disease), endocrine-disrupting effects (e.g., metabolic syndrome, obesity, diabetes), and reproductive effects (e.g., reduced semen quality, reduced gestational age, reduced birth weight) (Furlong et al, 2014; González-Alzaga et al, 2014; Saillenfait et al, 2015; Coker et al, 2018). Exposure to 2,4-dichlorophenoxyacetic acid (2,4-D) and 2,4,5-trichlorophenoxyacetic acid (2,4,5-T), the most commonly used PAs, is linked to wheeze, non-Hodgkin’s lymphoma, soft-tissue sarcoma, and age-related macular degeneration (Jayakody et al, 2015; Hoppin et al, 2017; Montgomery et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The occupational literature regarding visual or auditory effects of 2,4-D is also scarce. One study found that use of phenoxyacetate herbicides, including 2,4-D, was associated with higher odds of age-related macular degeneration in farmers in the Agricultural Health Study (U.S.) (Montgomery et al, 2017). To our knowledge, no auditory effects of 2,4-D exposure have been reported in farmers or pesticide applicators.…”
Section: Discussionmentioning
confidence: 85%